PELAYANAN KESEHATAN PASIEN RAWAT JALAN PADA PUSKESMAS MUARA SIKABALUAN KECAMATAN SIBERUT UTARA KABUPATEN KEPULAUAN MENTAWAI - Eva Suryani (Jurnal Public Administration, Business and Rural Development Planning, 2020)
This study aims to determine how the health care of outpatients in puskesmas and the factors that influence in the outpatient health services at Muara Sikabaluan Health Center, North Siberut District, Mentawai Islands District. This research uses descriptive method, in which the researcher tries to describe all phenomena, symptoms, events according to the research problem in a qualitative approach, by collecting data through interviews and observations and collecting basic data in accordance with the object under study. In this study, 12 respondents from Muara Sikabaluan Health Center employees and 2 respondents from the community/patients, a total of 14 respondents. The results obtained as a whole that the services provided by the Muara Sikabaluan Health Center have been going well and correctly but the results have not been maximized. Principles of service performed by Muara Sikabaluan Health Center based on MenPan No. 63 / KEP / M.PAN / 7/2003 regarding public services. The ten health service principles are only five service activities that have been successfully achieved - the simplicity of service procedures, information clarity, information certainty, service security and comfort services. While outpatient health services at Puskesmas Muara Sikabaluan which have not been maximized include easy access to difficult and risky Puskesmas, discipline, courtesy and friendliness, responsibilities, facilities and infrastructure as well as other supporting facilities and there are still found inaccuracies in service delivery both recording and reporting.